A Study on The Use of Smartphone Applications in English Language Learning with Special Reference to Covid-19 Pandemic - Bareq Raheem; Mohammad Danish Mahmood; G.M. Abu Taher; Zareen Shakeel (Newinera Publisher, 2022)
Technology and education are essential concepts in the current world. The societies of the world are heading towards technology and education very rapidly. Both the concepts indicate the hasty development taking place everywhere. The progress in the field of technology and education can be taken as a sign of growth in a particular society. The present study aims at explaining the use of smartphone applications to improve English language skills and translation and vocabulary improvement. This paper also seeks to demonstrate the significant role played by smartphone applications amid the COVID-19 pandemic. Through the present study, it has been demonstrated that smartphone applications aid in improving language skills, translation, and enriching vocabulary. Moreover, smartphone applications have been used virally amid the COVID-19 pandemic. They have a significant role in online teaching and learning. They act as a personal teacher who works 24/7.